Multidisciplinary "limb salvage" treatment of osteosarcoma. - L. Pochanugool (2018)
Intraarterial plus systemic chemotherapy of cis-diamine dichloroplatinum-II and anthracycline together with preoperative radiation and "limb salvage" treatment have increased the chance of local control and facilitated the previous surgically nonresectable to be resectable. Among 30 cases of osteosarcoma from 1986-1989, aged 9-43 years old, 10 of the 17 cases (58.8%) are still alive with the mean disease free survival of 27.8 months. Late pulmonary metastases cause the need for future protocol for prophylactic lung therapy.